Modernist theory : trimming the printed word : the instance of pre-modern Sinhala society - Roberts, Michael; International Centre for Ethnic Studies (Colombo : International Centre for Ethnic Studies, 2002)
On oral history of Sri Lanka.
Keywords: Sri Lanka -- Social conditions